A Theoretical Basis For Innovation, Institutions And Insurance Penetration Nexus - Hafiz, Usman Ahmed; Salleh, Fauzilah; Garba, Murtala (Advances in Social Sciences Research Journal, 2021)
Insurance is one of the systematic solutions to risk reduction available in the modern world. Its contribution to socio-economic development is difficult to overestimate, bearing in mind that the level of diversity and inclusion of the sector explains the degree of financial progress of a nation. This paper has a twofold objectives of ascertaining and discussing an overview of theories that stimulate economic performance from the angles of institutions and innovation. Keywords were used to search literature repository with the aid of Harzing’s publish or perish software. As a result of this process, the New Institutional Economics (NIE) and Schumpeter’s theory of Innovation found suitable to the objectives of the study. The paper concludes that efficient institutions coupled with the emergence of the novel products may likely promote trust and confidence in the market as well as specific needs of the large majority unserved potential consumers. Therefore, interaction between institutions and innovation could likely trigger insurance uptake.